(untitled) (Educational Dimension, 2021)
The article raises the question of the importance of reforming education in Ukraine, taking into account the peculiarities of the modern educational environment. The requirements to the modern educational space are generalized. The meaning of the term “pedagogical conditions” is clarified and the own definition of pedagogical conditions of the learning process is offered. The unity of the educational space, which consists of the environment, pedagogical conditions and personality, is established. The requirements to the modern educational space are generalized. External and internal factors, organizational and pedagogical, psychological and pedagogical factors influencing the learning conditions are singled out. The pedagogical conditions of multilingual didactics are researched and characterized: development and implementation of educational programs in foreign language teaching for profile school, taking into account individual request of students with orientation on the profile of education, formation of active and student’s own language position, use of methods aimed at development of polylingual competence, expedient use of modern information technologies. The article substantiates the priority of creating appropriate pedagogical conditions for the development of polylingual competence of students of professional schools in the modern educational environment.